Understanding the Role of Chaplains in Veteran Suicide Prevention Efforts: A Discussion Paper. (7th October 2014) - Kopacz, Marek S.; O'Reilly, Laurie M.; Van Inwagen, Chris C.; Bleck-Doran, Theodore L.; Smith, William D.; Cornell, Nancy
In recent years, identifying ways to mitigate the risk of suicidal behavior in Veteran populations has become a major public health challenge of special significance. This has included identifying support options that can be used by Veterans in times of distress or crisis. For example, Veterans at increased risk of suicide will sometimes voice complaints indicative of a need for spiritual and pastoral care support. At U.S. Department of Veterans Affairs Medical Centers, such support is provided to Veterans by clinical chaplains. This discussion paper aims to present the contextual framework in which chaplaincy services are provided to Veterans at increased risk of suicide, better conceptualize the spiritual and pastoral care needs of at-risk Veterans who request chaplaincy services, and offer practical suggestions for framing the provision of spiritual and pastoral care services.